Genetics of gene expression in primary immune cells identifies cell type-specific master regulators and roles of HLA alleles - Fairfax, B; Makino, S; Radhakrishnan, J; Plant, K; Leslie, S; Dilthey, A; Ellis, P; Langford, C; Vannberg, F; Knight, J (2012)
Trans-acting genetic variants have a substantial, albeit poorly characterized, role in the heritable determination of gene expression. Using paired purified primary monocytes and B cells, we identify new predominantly cell type-specific cis and trans expression quantitative trait loci (eQTLs), including multi-locus trans associations to LYZ and KLF4 in monocytes and B cells, respectively. Additionally, we observe a B cell-specific trans association of rs11171739 at 12q13.2, a known autoimmune disease locus, with IP6K2 (P = 5.8 × 10 -15), PRIC285 (P = 3.0 × 10 -10) and an upstream region of CDKN1A (P = 2 × 10 -52), suggesting roles for cell cycle regulation and peroxisome proliferator-activated receptor γ (PPARγ) signaling in autoimmune pathogenesis. We also find that specific human leukocyte antigen (HLA) alleles form trans associations with the expression of AOAH and ARHGAP24 in monocytes but not in B cells. In summary, we show that mapping gene expression in defined primary cell populations identifies new cell type-specific trans-regulated networks and provides insights into the genetic basis of disease susceptibility. © 2012 Nature America, Inc. All rights reserved.